Transverse vaginal septum in a teenager with a history of imperforate hymen: A case report - Lifa Lee; Mariko Matsuno; Sachino Kira; Sotaro Hayashi; Satoshi Nishiyama; Hiroshi Tsujioka (Elsevier, 2024)
Introduction: Imperforate hymen and transverse vaginal septum are conditions characterized by obstructive defects, typically leading to hematometrocolpos detected around the time of puberty. We encountered a patient who had undergone hymenotomy in infancy to treat pyocolpos due to an imperforate hymen and later developed hematometrocolpos in puberty due to a transverse vaginal septum. Case presentation: A 13-year-old female presented with hypomenorrhea and hematometrocolpos-induced dysmenorrhea. She had a history of pyocolpos with a urinary tract infection at 3 months of age. At that time, no vaginal opening was found on perineal examination, and imperforate hymen was diagnosed. When hymenotomy was performed, the external cervical os was not detected by intravaginal bronchoscopic examination. However, this abnormal finding was not fully investigated. The postoperative course after hymenotomy was free of complications, and the patient remained asymptomatic until menarche. When she presented 3 months after menarche, genital examination revealed a bulging transverse septum inside the vagina, 5 cm from the hymen. Ultrasound and magnetic resonance imaging revealed a distended uterus, distended upper vagina, and collapsed lower vagina. Transverse vaginal septum was considered, and vaginoscopy was performed to exclude vaginal reclosure or adhesion caused by the previous surgery. A diagnosis of transverse vaginal septum was confirmed, and total excision of the septum was performed. The patient underwent regular postoperative follow-ups for stenosis prevention. Conclusion: Considering the rarity of these concurrent conditions, clinicians must always consider the possibility of several complex anomalies. Vaginoscopy using a hysteroscope may be useful for definitive diagnosis and determining appropriate treatments.